SIKAP MASYARAKAT PASCA BANJIR LAHAR DINGIN (STUDI FENOMENOLOGIS PADA MASYARAKAT KELURAHAN TUBO) - Iskar Hukum; Eko Siswono; Uswatun Khasanah (Universitas Khairun, 2019)
This study aims to obtain the essence of community experience related to the change in attitude experienced after the natural disaster of cold lava flood in Kelurahan Tubo, Kota Ternate Utara, Ternate City. The research methodology used by researchers in this study is a qualitative research methodology with a phenomenological study approach. In the phenomenological tradition that is most labored by researchers is the essence of experience experienced by informants. Dimensions are important in phonomenology, first that in every human experience there is something essentially essential and meaningful. In-depth interviews and Focus group discussions aim to complete informants 'answers in accordance with the researchers' questions, in addition to in-depth interviews and focus group discussions can bring researchers closer to the community.